2006
DOI: 10.1088/0953-4075/39/4/002
|View full text |Cite
|
Sign up to set email alerts
|

Excitation energies, hyperfine constants, E1 transition rates and lifetimes of 4s2nlstates in neutral gallium

Abstract: Energies of the 4s2npj (n = 4–8), 4s2ns1/2 (n = 5–8), 4s2ndj (n = 4–7), 4s2nfj (n = 4–5) and 4s25gj states in neutral gallium are obtained using a relativistic many-body perturbation theory (RMBPT) method. First-, second-, third- and all-order Coulomb energies and first-order Breit and second-order Coulomb–Breit corrections are calculated. Reduced matrix elements, oscillator strengths, transition rates and lifetimes are determined for the 130 possible electric-dipole transitions. Hyperfine constants A are det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…High-frequency tails have been observed in all spectra analysed in this experiment, resulting from AC Stark shift effects induced by the high power of the ionization laser. Although recent studies have suggested these distortions can be removed by delaying the ionization laser light [34], the short lifetime of the 5s 2 S 1/2 state (t 1/2 = 5.7(6) ns [35]) did not permit this. Therefore, asymmetric fitting profiles defined by a Gaussian function with a power-law high-frequency tail were used (colloquially referred to as the Crystal Ball function) [36,37].…”
Section: Analysis and Resultsmentioning
confidence: 96%
“…High-frequency tails have been observed in all spectra analysed in this experiment, resulting from AC Stark shift effects induced by the high power of the ionization laser. Although recent studies have suggested these distortions can be removed by delaying the ionization laser light [34], the short lifetime of the 5s 2 S 1/2 state (t 1/2 = 5.7(6) ns [35]) did not permit this. Therefore, asymmetric fitting profiles defined by a Gaussian function with a power-law high-frequency tail were used (colloquially referred to as the Crystal Ball function) [36,37].…”
Section: Analysis and Resultsmentioning
confidence: 96%
“…A comprehensive all-order study of atomic properties of the 4s 2 nl states of neutral gallium and 4s 2 4p states of Ga-like ions was conducted in Refs. [75,78]. A comparison of the third-order and all-order SD results for the ground state energies of Ga, Ga-like ions, and Tl with experiment is given in Table 10.…”
Section: All-order Calculationsmentioning
confidence: 99%
“…Available experimental and theoretical data are quite limited for high Rydberg states. Therefore, our lifetime results obtained from the WBEPM theory have been compared with relativistic many-body perturbation theory (RMBPT) results given by Safronova et al [24] and the results of Carlsson et al including both experimental and theoretical data [25]. 3 80 9 45536 45530 129 135 111 136 10 46274 46269 192 200 169 204 11 46758 46754 270 250 247 257 12 47093 47090 367 346 13 47334 47332 482 476 14 47514 47512 618 15 47651 47650 775 16 47758 47757 955 17 Carlsson et al employed experimental laser spectroscopic techniques.…”
Section: Results and Conclusionmentioning
confidence: 98%